Measuring Sustainable Leadership Effectiveness in Facing the Challenges of a Complex Business Environment - I Wayan Adi Pratama; I Wayan Jata; Nyoman Gede Mas Wiartha; Made Darmiati; Khoiruddin Khoiruddin (West Science Business and Management, 2023)
Sustainable leadership, situated at the intersection of leadership theory and sustainability principles, has emerged as a critical focal point for addressing the multifaceted challenges of contemporary business environments. This study conducts a comprehensive bibliometric analysis to measure the effectiveness of sustainable leadership in navigating the complexities of the business landscape. The analysis draws on a diverse range of academic sources from prominent databases, uncovering key publication trends, influential authors, citation patterns, and emerging themes. The results reveal a substantial growth in the literature on sustainable leadership over the past two decades, underscoring its increasing importance. Highly cited publications such as Hughes et al.'s seminal work on leadership and Cobb & Daly's treatise on redirecting the economy for community and sustainability have played pivotal roles in shaping the field. The analysis also highlights distinct research clusters, including those focusing on ethical leadership, transformational leadership, and entrepreneurial leadership in the context of sustainability. The prevalence of terms such as "sustainability leadership," "performance," and "impact" underscores the centrality of leadership in driving sustainable practices. Conversely, terms like "reputation" and "servant leadership" emerge with fewer occurrences, signaling potential areas for deeper exploration. In conclusion, this bibliometric analysis provides valuable insights into the evolving landscape of sustainable leadership research, offering a roadmap for future studies and practical applications in the pursuit of sustainable business practices.